2018
DOI: 10.4236/aad.2018.73006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Usefulness of Carbon Nanotubes as Antiviral Compounds for Treating Alzheimer Disease

Abstract: The new generations of nano-devices successfully apply with great promise as drug carriers in the treatment of different diseases. The proposed model aims to determine the pharmacological targets and evaluate the bio-safety of usefulness of carbon nanotube conjugated with two different antiviral compounds, Acetylcholine and Ravastigmine, for treating Alzheimer disease. We also obtain the medicinal model mathematically to evaluate the interaction energy arising from encapsulation of each antiviral compound insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Genetic material can be delivered to the nucleus and cells with high efficiency using carbon nanotubes. The few studies on CNTs for AD treatment are still in the early stages and need to be further tested for their ability to cross the BBB ( Garalleh, 2018 ; Mishra et al, 2021 ). However, CNTs can be used as biosensors with high sensitivity and selectivity to detect Aβ in human serum, particularly Aβ42 and Aβ40 peptides ( Chen et al, 2022 ).…”
Section: Types and Properties Of Nanomedicinementioning
confidence: 99%
“…Genetic material can be delivered to the nucleus and cells with high efficiency using carbon nanotubes. The few studies on CNTs for AD treatment are still in the early stages and need to be further tested for their ability to cross the BBB ( Garalleh, 2018 ; Mishra et al, 2021 ). However, CNTs can be used as biosensors with high sensitivity and selectivity to detect Aβ in human serum, particularly Aβ42 and Aβ40 peptides ( Chen et al, 2022 ).…”
Section: Types and Properties Of Nanomedicinementioning
confidence: 99%
“…Zhang et al give the possibility of CNT to be used as carrier for DNA vaccine since 23.8% increase in the immune protective effect by SWCNTs for unmodified DNA vaccine [ 39 ] Al Garalleh et al reported that the antiviral drug Ravastigmine could be encapsulated by SWCNT having a radius greater than 3.39 Angstrom. SWCNT was also reported to have direct effect of reducing the defense mechanism of influenza A virus H1N1 [ 40 ].…”
Section: Role Of Nanotechnology In the Management Of Viral Diseasesmentioning
confidence: 99%